Comparative analysis of URL shortening algorithms: performance considerations in the application domain of web search and information retrieval technology - Kyrychenko, I.; Shamrai, Ye. (ХНУРЕ, 2022)
This article provides an in-depth overview and comparative analysis of URL shortening algorithms, with a focus on their performance and security. URL shortening is an important tool for creating concise versions of long URLs, particularly in platforms with character limitations. However, the increasing prevalence of cyber threats has raised concerns regarding the security of URL shortening. The paper examines a range of URL shortening algorithms, including Hash-based and Randomized algorithms, and compares their effectiveness based on factors such as URL length, randomness, and resistance to brute-force attacks. In addition, the article explores the security risks involved in URL shortening and suggests strategies for mitigating them. The paper also includes a performance analysis of different URL shortening algorithms, considering the time required to generate a shortened URL and redirect the user to the original URL. Finally, the article discusses the challenges of evaluating URL shortening algorithms and outlines potential avenues for future research in this area. У цій статті представлено детальний огляд і порівняльний аналіз алгоритмів скорочення URL-адрес з акцентом на їхню продуктивність і безпеку. Скорочення URL-адрес є важливим інструментом для створення стислих версій довгих URL-адрес, особливо на платформах з обмеженнями на кількість символів. Однак, зростаюча поширеність кіберзагроз викликає занепокоєння щодо безпеки скорочення URL-адрес. у статті розглядається низка алгоритмів ско рочення URL-адрес, включаючи алгоритми на основі хешування та рандомізовані алгоритми, і порівнюється їхня ефективність на основі таких факторів, як довжина URL-адреси, випадковість та стійкість до атак грубої сили. Крім того, в статті досліджуються ризики для безпеки, пов'язані зі скороченням URL-адрес, і пропону ються стратегії для їх зменшення. Стаття також містить аналіз продуктивності різних алгоритмів скорочення URL-адрес, враховуючи час, необхідний для генерації скороченої URL-адреси і перенаправлення користувача на оригінальну URL-адресу. нарешті, в статті обговорюються проблеми оцінки алгоритмів скорочення URL адрес і окреслюються потенційні шляхи для майбутніх досліджень у цій галузі.
Keywords: URL shortening algorithms; randomized algorithms; performance evaluation; hash-based algorithms; security considerations